Oxidative Stability of Baru (Dipteryx alata Vogel) Oil Monitored by Fluorescence and Absorption Spectroscopy - Vanessa D. Silva; José N. Conceição; Ivan P. Oliveira; Caroline H. Lescano; Rozanna M. Muzzi; Omar P. S. Filho; Edemilson C. Conceição; Gleison A. Casagrande; Anderson R. L. Caires (Journal of Spectroscopy)
Baru (Dipteryx alata Vogel) is a native fruit of the Brazilian savanna that provides a nutritive oil, which also has medicinal properties. Baru fruits were collected in central-western Brazil, and the oil was obtained by pressing the seeds. The Baru oil was heated at 110°C for 24 h, and its oxidative stability was investigated by using fluorescence and absorption spectroscopy. The data showed that both absorption and fluorescence were able to precisely monitor the oil degradation induced by the thermooxidative process. The results revealed a rapid growth of the primary compounds generation in the first 16 hours of degradation. Significant amounts of secondary compounds began to be generated after 14 hours.